Timurid princess The image of time and spirit in the image of Saraymulkhanim (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
Marrying the Timurid princes to suitable brides, an even more delicate matter: transferring the daughters of the master to appropriate places at the right time, an unbearable tragedy: for the young and beautiful brides who were left behind due to the untimely death of both the crown prince and the grandson of the crown prince. The responsibility of being a mother-in-law, mother, and friend was also on Mrs. Saraymulk. He had the sense to put everything in place and do it according to the Master's wishes. Besides, the women in Sahibgiron's harem respected Bibikhanim too .